Common and distinct neural correlates of personal and vicarious reward: A quantitative meta-analysis - Morelli, Sylvia A.; Sacchet, Matthew D.; Zaki, Jamil (NeuroImage (Orlando, Fla.), 2015)
Individuals experience reward not only when directly receiving positive outcomes (e.g., food or money), but also when observing others receive such outcomes. This latter phenomenon, known as vicarious reward, is a perennial topic of interest among psychologists and economists. More recently, neuroscientists have begun exploring the neuroanatomy underlying vicarious reward. Here we present a quantitative whole-brain meta-analysis of this emerging literature. We identified 25 functional neuroimaging studies that included contrasts between vicarious reward and a neutral control, and subjected these contrasts to an activation likelihood estimate (ALE) meta-analysis. This analysis revealed a consistent pattern of activation across studies, spanning structures typically associated with the computation of value (especially ventromedial prefrontal cortex) and mentalizing (including dorsomedial prefrontal cortex and superior temporal sulcus). We further quantitatively compared this activation pattern to activation foci from a previous meta-analysis of personal reward. Conjunction analyses yielded overlapping VMPFC activity in response to personal and vicarious reward. Contrast analyses identified preferential engagement of the nucleus accumbens in response to personal as compared to vicarious reward, and in mentalizing-related structures in response to vicarious as compared to personal reward. These data shed light on the common and unique components of the reward that individuals experience directly and through their social connections. [Display omitted] •We compare quantitative meta-analyses of personal and vicarious (vic.) reward.•Vic. reward studies activate regions related to value computation and mentalizing.•Vic. and personal reward studies commonly activate ventromedial PFC.•Personal as compared to vic. reward preferentially engages nucleus accumbens.•Vic. versus personal reward preferentially engages regions related to mentalizing.